Pakaian Pantas Perempuan dalam Ibadah di Gereja: Antara Ketaatan dan Tekanan Sosial - Pitemo, Yulice; Labito, Alce Mariani; Lembolangi, Lefran (MARSAHALA : Jurnal Studi Agama dan Budaya, 2025)
This study aims to analyze the influence of women’s perceptions regarding appropriate attire for worship in church and how this affects their participation in religious activities. A quantitative approach was used with a survey method, gathering data through questionnaires distributed to women in the Sinear Batangbabasal Congregation. The data were analyzed using descriptive analysis to identify perception patterns and their relationship with participation levels. The results show that perceptions of appropriate attire—characterized by simplicity, modesty, and formality—are positively correlated with women’s participation in worship. Women who feel that their attire meets the church’s standards are more motivated to engage in church activities. However, the findings also indicate the presence of social pressure related to dress expectations, which may lead to anxiety, social inequality, and fragmentation within the church community. In conclusion, while dress standards can strengthen unity in the church, attention must be given to the social and economic diversity of the congregation to foster inclusive acceptance. This study suggests that the church should balance dress norms with respect for the social and economic conditions of individuals.